Pengaruh Dance Movement Therapy terhadap Perubahan Tekanan Darah pada Lansia Hipertensi - Supriadin Supriadin; Agung Waluyo; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of dance movement therapy on changes in blood pressure in hypertensive elderly. The research design used a quasi-experimental pre-post control group. The results showed a significant difference in changes in systolic and diastolic blood pressure after being given dance movement therapy (t = 2.781, p = 0.013), t = 2.465, p = 0.025), as well as changes in systolic and diastolic blood pressure after the intervention at control group (t = 1.458, p = 0.163), t = 0.606, p = 0.552). In conclusion, dance movement therapy can significantly reduce systolic blood pressure in hypertensive patients. Keywords: Dance Movement Therapy, Primary Hypertension, Blood Pressure